The Politics of Immigration in Multi-Level States
XV, 304 p.
Keywords: This book develops an exploratory theory of immigration in multilevel states addressing two themes: governance and political parties. It examines not only how, and by whom, immigration policy is decided and implemented at different levels, but also how it has become a key-issue of party competition across multilevel states.